Do Attitudes, Mental Health Status, and Interpersonal Factors Predict COVID-19 Vaccine Hesitancy at the Early Phase of the Pandemic? A Longitudinal Study in Chinese College Students - Wu, Zhipeng; Wang, Xin; Zhang, Sha; Ding, Nani; Zhang, Guohua; Zhao, Chengjia; Xu, Huihui; Lai, Xinyi; Tu, Xiaolian; Yang, Xue (Frontiers in Psychology, 2022)
Purpose: The present study examined whether and how attitudes towards the COVID-19 vaccine (i.e., safety, efficacy, and price), mental health statuses (i.e., perceived stress and depression), and interpersonal factors (i.e., online social support, perceived social support) would predict COVID-19 vaccine hesitancy. Patients and methods: The two-wave longitudinal surveys were conducted in December 2019 and 2020 in Chinese medical college students (N=194). Well-validated measures were used, including the Perceived Stress Scale, the Center for Epidemiologic Studies Depression Scale, the Online Social Support Questionnaire, and the Perceived Social Support Scale. Perceived safety, efficacy, price of COVID-19 vaccine, vaccine hesitancy, and actual intake were also measured. Results: Only 2.1% of participants had been vaccinated against COVID-19 in the early stages of the pandemic; 13.4% intended to get vaccinated in the next 3 months, and 66% intended to have it in the next 12 months upon follow-up. Multiple regression analyses revealed that perceived stress (βm = -0.15, p < 0.05) and depression (βm = -0.15, p < 0.05) were risk factors for positive attitudes towards the COVID-19 vaccine; online social support (ORm = 1.41, p < 0.01) and positive attitudes towards the COVID-19 vaccine (ORm = 1.83, p < 0.01) were protective factors of intention to get vaccinated in future. Conclusion: Findings suggest that intervention efforts should be made to reduce negative attitudes towards the COVID-19 vaccine among people with poor mental health and enhance online social support to promote COVID-19 vaccination.